Dead Center: Berlin, the Postmodern Gothic, and Norman Ohler's Mitte - Steffen H. Hantke (Studies in 20th & 21st Century Literature, 2006)
Cultural critics often frame present-day Berlin as a space of historical discontinuities, a nexus of modernity and postmodernity that, in its orientation toward the future, represents post-reunification Germany in all its complexity. However, this framing tends to suppress Gothic imagery, of which traces can be found in the critical discourse on the city. Recuperating such Gothic tropes from critical discourse, and then consciously and strategically re-deploying them, can be a valuable strategy for opening up new venues of thinking about the lingering presence of the past, the high cost of modernization, and the uncanny emotional and affective dimensions of urban space. While this project of recuperation has been taken on in some critical analyses of Berlin, most notably among them Brian Ladd's The Ghosts of Berlin (1997), it is the new German literature on Berlin that proceeds more boldly into the terrain of the Gothic. Among this new "Berlin literature," Norman Ohler's critically acclaimed Gothic novel Mitte (2001) stands out as a cogent analysis of the new Berlin and of the problems of inhabiting a decentralized urban space and reconnecting it to authentic historical experience.
Keywords: present-day Berlin; Berlin; historical discontinuities; discontinuities; modernity; post-reunification Germany; Germany; Gothic imagery; Gothic; past; urban space; Brian Ladd; The Ghosts of Berlin; new German literature; Norman Ohler; Mitte; new Berlin; urban; authentic historical experience; experience